Tuberous Sclerosis Complex and Arachnoid Cysts - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs)
Investigators at the Massachusetts General Hospital, Boston, MA, and Universitat Autonoma de Barcelona, Spain, assessed the prevalence and characteristics of arachnoid cysts in a cohort of 220 patients with tuberous sclerosis complex (TSC).